2016
DOI: 10.1136/sextrans-2016-052773
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in the HIV care cascade and barriers to antiretroviral therapy uptake among female sex workers in Port Elizabeth, South Africa: findings from a respondent-driven sampling study

Abstract: HIV testing and awareness of HIV status were high, but substantial losses in the cascade occur at treatment initiation. Given that FSWs engaged in mobile HIV testing and peer education programmes have unmet HIV treatment needs, models of decentralised treatment provision such as mobile-based ART care should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 19 publications
3
80
2
Order By: Relevance
“…We also did not vary our input costs in the uncertainty analysis, and the costs of the novel testing modalities that have not been implemented at scale in the public sector (in particular self-test distribution) are currently based on assumptions regarding staff time, linkage and the number of tests that can be performed per day. Rates of linkage to ART after diagnosis are difficult to determine in the context of community-based models of HIV testing, which generally suffer from lower rates of linkage than facility-based testing 18,[49][50][51] . In our uncertainty analyses, we found that in most community-based testing scenarios the cost per life year saved declined substantially as the rate of linkage to ART increased (Table S3.11), and it is therefore important to quantify linkage rates more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not vary our input costs in the uncertainty analysis, and the costs of the novel testing modalities that have not been implemented at scale in the public sector (in particular self-test distribution) are currently based on assumptions regarding staff time, linkage and the number of tests that can be performed per day. Rates of linkage to ART after diagnosis are difficult to determine in the context of community-based models of HIV testing, which generally suffer from lower rates of linkage than facility-based testing 18,[49][50][51] . In our uncertainty analyses, we found that in most community-based testing scenarios the cost per life year saved declined substantially as the rate of linkage to ART increased (Table S3.11), and it is therefore important to quantify linkage rates more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges in uptake of and adherence to HIV services for FSWs have been well-documented. 26,27 There are additional challenges facing younger women, including lack of knowledge, limited social/economic empowerment, and autonomy. [28][29][30] In addition, there may be competition and mistrust between older and younger FSWs, which may result in younger women failing to access services designed for adults.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, female sex workers (FSWs) living with HIV have sub-optimal usage of antiretroviral treatment (ART); approximately 38 to 52 percent of FSWs living with HIV are on treatment (Mountain et al 2014;Lancaster et al 2016;Schwartz et al 2017). Research in Tanzania has documented the challenges FSWs face in accessing HIV care and treatment services, including out-of-pocket costs associated with care, reaching distant clinics, lack of awareness and misperceptions of treatment, and dual stigma associated with sex work and HIV (Tomori et al 2014).…”
Section: Executive Summarymentioning
confidence: 99%